Development and Optimization of Andrographis paniculata Extract-Loaded Self-Microemulsifying Drug Delivery System Using Experimental Design Model - Chaiyakarn Pornpitchanarong; Prasert Akkaramongkolporn; Nattawat Nattapulwat; Praneet Opanasopit; Prasopchai Patrojanasophon (Pharmaceutics, 2024)
The objectives of this study were to develop an optimized formulation for an Andrographis paniculata extract (AGPE)-loaded self-microemulsifying drug delivery system (SMEDDS) using an experimental design and evaluate the characteristics of the developed SMEDDS. The solubility of andrographolide (AGP) in various solvents was investigated. The pseudo-ternary phase was constructed to provide an optimal range for each component to form microemulsions (MEs). The formulation was optimized using an I-optimal design mixture type, where the physical stability, droplet size, polydispersity index, and zeta potential were examined. Soft capsules of the optimized AGPE-loaded SMEDDS were manufactured. The dissolution and ex vivo membrane permeation were studied. Oleic acid, Tween® 80, and PEG 400 were the best solubilizers for AGP. The promising surfactant to co-surfactant ratio to generate ME was 3:1. The optimized SMEDDS contained 68.998% Tween® 80, with 13.257% oleic acid and 17.745% PEG 400. The assayed content of AGP, uniformity of dosage unit, and stability complied with the expected specifications. The dissolution and membrane permeability of AGPE-loaded SMEDDS was significantly improved from the A. paniculata extract (p < 0.05). All in all, the developed optimized AGPE-loaded SMEDDS was proven to contain optimal composition and AGP content where a stable ME could spontaneously be formed with enhanced delivery efficacy.